Between consensus and the “tax agreement” provided for in the draft of the Tax Ordinance of June 4, 2019 - Tsima, Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
A change in the perception of the relationship between the tax debtor and the tax creditor is necessary. The regulation of non-governing forms of operation of tax authorities is the normative basis that determines the change in the way in which tax matters are dealt with. This article reviews the proposal for consensual resolution of disputes contained in the draft of the Tax Ordinance of March 8, 2019. In this draft, a chapter entitled “Tax agreement” was included, which is devoted entirely to the structure of the tax agreement. However, to what extent does the outlined legal structure of the tax agreement make it possible to create a negotiating space between the taxpayer and the tax authority? The consensuality that the parties strive for should foster the pursuit of the private interest in the optimal dimension and, at the same time, should not affect the public interest. This is possible. In this way, the equality of parties manifests itself in the framework of consumer contracts where the entrepreneur’s party is stronger or on the level of repressive law for example, in criminal law — where, as indicated, the consensual way of settling the matter should not disqualify the aspiration to equalize the position of all participants of this consensus. The position defended by the present author is that obtaining a contractual agreement in tax law based on a consensus assuming the parity of parties does not exclude the possibility of pursuing a fiscal interest.
Keywords: ordynacja podatkowa; umowa podatkowa; prawo publiczne; prawo prywatne